Wanda: A Framework to Develop Card Based Games to Help Motivate Programming Students - Drumond, Rafael Rego; Brandao, Andre; Salles, Carlos (2014 Brazilian Symposium on Computer Games and Digital Entertainment, 2014)
Teaching computer science, algorithms and other programming subjects can be stressing and difficult. Students motivation might drop due to the difficulty of learning how to program. To deal with this matter, this paper presents Wanda, a simple framework created to build specific card-based games that can be used as educational tools. With Wanda, professors can create educational electronic card games that require students to create virtual agents to play them. These games can help teachers and tutors to motivate programming students.